INDUSTRI HALAL BERKONTRIBUSI TERHADAP PERTUMBUHAN EKONOMI DI ERA PANDEMI COVID-19: PELUANG DAN TANTANGAN - Dewi Utari; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
This study focuses on analyzing how the halal industry affects economic growth in the Covid-19 pandemic era. This study also identifies opportunities as well as challenges in its development. The method used in this study is a descriptive qualitative approach with library research. This study finds that the halal industry has a major role in the development of economic growth, as evidenced by the halal industry has contributed USD 3.8 billion to Gross Domestic Product (GDP) and investment of USD 1 billion from foreign investors in 2019. The halal industry also has opportunities in various sectors, namely halal food and beverages, halal tourism, halal fashion, halal cosmetics, halal media and recreation, halal pharmacy and halal finance. However, Indonesia must face various challenges, namely, challenges from the government, organizations, development, existing resources, and challenges that come from the community/consumers